Analysis of total burn surface area from bleve fireball impact at dynamic parameter condition - Mohd Zaidi, Aiman Hazim (2019)
Feyzin disaster during 1966 in France will always leave a big mark in engineering industry as it involved many casualties. The disaster would make a perfect example of case study on impact of BLEVE fireball towards nearby occupants. The methodology to investigate BLEVE’s characteristic, fireball’s impact toward the effect of TBSA to human during Feyzin incident is by using BLEVE’s dynamic model in the analysis. All scenarios involved during the analysis such as sphere tank design, chronology of accidents, and other relevant input is based on ARIA Feyzin incident report. The probability of occupants and the thermal dosage required for the fire personnel to get caught on fire and suffers different type of burns are determined with different distance from fireball. TBSA charts and age from JP Bull is simplified to RSM model, to determine the burn surface area on human’s body. Next, 150 rescue personnel who were standing 100 to 120 meter from the centre of explosions will be investigated to determine the real possibility of mortality rate with the reported casualties. The results of the analysis found that it would take at least 32,000,000 kW/h of thermal dosage required for a victims to be inflicted with deaths. However, the model use did not have the same result as the real casualties reported. New models need to be invented to get a proper reported casualties.